Kelayakan Finansial Usaha Kambing Kacang (Capra Aegagrus) Berdasarkan Skala Pemeliharaan di Kabupaten Takalar : Financial Feasibility of Peanut Goat (Capra Aegagrus) Business Based on Maintenance Scale in Takalar Regency - Paly, Muhammad Basir (Anoa: Journal of Animal Husbandry, 2023)
The feasibility of a pea goat business based on a scale of maintenance is important. This is because goats have a fairly wide market share, ranging from the needs of meat consumption to the needs of aqiqah and sacrificial animals. This research aims to evaluate the viability of Peanut goat farming through the feasibility indicators of Break Event Point (BEP), Net Present Value (NPV), and Benefit Cost Ratio (B/C ratio) based on the ownership scale. The study was conducted in Sanrobone Takalar from April to July 2023. A survey method was employed, involving 60 households of goat farmers as the sampling units. These households were categorized into four ownership scales: 2-5 goats, 6-9 goats, 10-13 goats, and ≥14 goats. The measured and analyzed variables included cash flow, BEP, NPV, and B/C ratio. The research findings indicate that the ownership scales of 6-9 goats, 10-13 goats, and ≥14 goats have BEP values >1 and B/C ratios >1. On the other hand, the smaller scale of 2-5 goats shows BEP <1 and B/C ratio <1. In terms of the NPV indicator, positive values (>1) were obtained for all ownership scales, indicating the potential profitability of Peanut goat farming. In conclusion, this study suggests that all ownership scales are considered feasible, yet based on the BEP and B/C ratio indicators, the ownership scales deemed feasible are 6-9 goats, 10-13 goats, and ≥14 goats.